Correction: Mental health status and the quality of life of infertile women receiving fertility treatment in Bangladesh: A cross-sectional study. - PLOS GLOBAL PUBLIC HEALTH Staff (PLOS Global Public Health)
[This corrects the article DOI: 10.1371/journal.pgph.0002680.].